Outcomes of urine sodium guided diuresis in acute heart failure: a preliminary analysis - C Chelfi Zhi, Fei Chua; B. K., Chung; Hwei Sung, Ling; C. S. K, Hoon; Yee Ling, Cham; Alan Yean Yip, Fong; T. K., Ong (European Society of Cardiology, 2025)
Background: Urine sodium level has been proposed as an indicator to guide diuretic regime to relieve congestion in acute heart failure (AHF). However, the experience and evidence of urine sodium guided diuresis is limited in real world practice. Objectives: This study aims to compare diuretic outcomes, including urine volume and diuretic regime between patients with and without urine sodium level measured. Methods: A total of 114 patients were included, divided into UrineNa (n=29) and Non-UrineNa (n=85) groups. For UrineNa group, urine sodium level was taken two hours after first furosemide dose was given. Demographic data, clinical parameters such as blood pressure, heart rate, urine output, creatinine levels, furosemide dose, and other diuretic use as well as comorbid conditions were analyzed. Urine volumes were measured at 6 and 24 hours post first furosemide dose given. Results: This is our preliminary result. The mean age, gender distribution and key clinical parameters such as systolic and diastolic blood pressure, heart rate were comparable between the groups. Similarly, the prevalence of comorbid conditions, including hypertension, diabetes, dyslipidemia, ischemic heart disease, and chronic kidney disease, did not sign ificantly differ between groups. There were no significant differences in mean creatinine (urineNa, 143 mmol/L versus Non-UrineNa, 141 mmol/L, p=0.294) and urea (urineNa, 9.5 mmol/L versus Non-UrineNa, 8.9 mmol/L, p=0.294) between the two groups. There were also no significant differences in mean urine output at 6 hours (urineNa, 1520 ml versus Non-UrineNa, 1419 ml, p=0.294) and 24 hours (urineNa, 2874 ml versus Non-UrineNa, 2877 ml, p=0.763) after the first furosemide dose between the two groups. The first 24 hours furosemide doses (urineNa, 124mg vs. Non-UrineNa, 133mg, p=0.447) and use of adjunct diuretics were also comparable (p=0.417). Mortality rates were no different in both group (p=0.234). Conclusion: The study found no significant differences in diuresis between cases with and without urinary sodium measurement guidance in the 1st 24 hours of AHF admission. However, these preliminary findings may not reflect the final outcome until the study is fully completed.